Assessment of soil nature and control mechanism for rill erosion in a hilly slope area at Ambo town, Oromia region, Ethiopia – An overview - THANAPPAN SUBASH; A. DHANASEKARAN; K. SATHYA PRABHA (International Journal of Pharma and Bio Sciences, 2018)
The main objectives of the current study on examining the physical and chemical characteristics of the regional soil, ascertain the soil fertility, finding the annual soil erodibility rate and the annual soil loss and thus, to suggest the most suitable and appropriate control mechanism for soil conservation practices which could directly empower the agricultural activities, integrated water management, income potential of the region and the sustainable development. The current overview on the geological assessment of soil will definitely provide an opening for the clear understanding of the nature of soil and their impact on soil nutrients and crop productivity. The test on the rills with the available ingredients through the visual observation will help in deciding the control mechanisms to overcome the erosion problems. The study would provide information for the kebele administration office and society the factors responsible for soil erosion and would help delineating management strategies to protect the soil from further damage. The study would help enhancing the productivity of soil quality and crop productivity.